ANALISIS DAMPAK SUPERVISI KELAS TERHADAP KUALITAS KINERJA PENDIDIK - Cecep Abdul Muhlis Sujai (HASBUNA : Jurnal Pendidikan Islam, 2022)
One component that functions meaningfully in achieving educational goals is educational supervision. Education Supervision is a very meaningful job in improving the quality of education. The quality of education is closely related to the professionalism of educators in experiencing current and future educational problems. This study aims to determine the description of the principal's supervision in improving the performance of educators, supporting faktors, and inhibiting faktors in the implementation of supervision, especially in terms of 1) Implementation of Principal Class Supervision in Improving Educator Performance; 2) Results of Principal's Class Supervision in Improving Educator Performance. The method used in this study uses a qualitative method. A qualitative method as a research procedure that presents descriptive data in a few words written or spoken by people or actors that can be observed. Qualitative research is used to reveal descriptive data from information about what they do and what they experience towards the research focus.